Da cientificidade da pedagogia no Brasil: a identidade do pedagogo em debate - Brito, Flávio Rafael da Silva (2023)
The present research, of a philosophical-educational nature, with qualitative nature, developed with theoretical-bibliographic and documentary support, explains and analyzes the dichotomy that occurs during Pedagogy in Brazil and that is configured in the counterpoint of what is proposed by the specific legislation with the theoretical foundations that defend the scientific character of Pedagogy. The objective was to identify, question and debate the principles and epistemological foundations of Pedagogy in Brazil, in order to understand whether the principles deviate Pedagogy from the scientific statute. The theoretical framework of this research is composed by Libâneo, Marques, Severino, Saviani, Franco, Pimenta, Schmied-Kowarzik, Morin, Houssaye among others. To this end, a literature review was carried out, through the analysis of dissertations and theses between the period 2016-2021, to understand how the theme of the scientificity of Pedagogy has been approached by scientific research in the area of education. Next, a historical survey was carried out, through documentary and bibliographical sources, which regulate and portray the Pedagogy course in Brazil, with the objective of identifying the principles and epistemological foundations that govern the formative practice in these courses. In the literature review, we found that the research carried out in the area of education, on Pedagogy, although abord were the ambiguities and contradictions that permeate the Pedagogy course, did not discuss the question of its scientificity. The reason for the lack of interest in the issue was understood in the historical survey. Throughout history, Pedagogy has been denied as an area of knowledge, having its object of investigation, education, transferred to other areas of knowledge, called the sciences of education, whose scientificity was already recognized, for meeting the epistemological paradigms s of positivism. In Brazil, the tradition of pedagogical training was no different. Submitted to the knowledge of the educational sciences, Pedagogy was gradually no longer dealing with educational issues to deal with teaching issues, assuming a pragmatic, technical and instrumental identity. Increasingly involved in ambiguities and contradictions, the lack of clarity and identity of the course almost led to the extinction of the academic space of Pedagogy in Brazil. However, in the theoretical field, Pedagogy was still understood as an area of education. Gradually, given the importance of education for social development, with the expansion of public education, Pedagogy had its identity subsumed to teaching. Thus, the hypothesis that the principles and epistemological foundations of Pedagogy in Brazil deviate from its scientific status is confirmed. Given this finding, a critical, dialectical and complex conception of the educational phenomenon is proposed and the rescue of the epistemological principles and foundations that give Pedagogy its scientific identity, recognizing it as the only science capable of overcoming the dilemma between theory and practice in the teaching-learning process. For this, a proposal for ref the course formulation is presented, rescuing its principles and theoretical-epistemological foundations through a solid formation of scientific, technical and teaching ballast, capable of articulating the necessary sabers to formulate a true theory of education. It is hoped in this way to contribute to the consolidation of an authentic science of education. Thus, the relevance of this research is demonstrated, to contribute to the elucidation of the scientific status of Pedagogy, characterizing the specificity of its knowledge, its formation and its field of action.